The impact of students’ misperceptions on test performance: A 3p model and self-determination theory approach - Fraidan, Abdullah Al (Edelweiss Applied Science and Technology, 2024)
This research investigates the complex relationship between students’ misperceptions about their teachers and exams, test anxiety, and their overall test performance, framed through a newly proposed Presage, Process, Product (3P) model and Self-Determination Theory (SDT). Specifically, it explores how students’ misperceptions formed during the presage phase disrupt Basic Psychological Needs (BPN) for autonomy, competence, and relatedness, negatively influencing their test-taking strategies and performance outcomes. The study adopts a theoretical approach, proposing a conceptual framework rather than collecting empirical data, to illustrate the potential dynamics between misperceptions, test anxiety, and academic achievement. A key feature of the new 3P model is the two-way interaction between the process and product phases, illustrating how the test-taking behaviors (process) influenced by misperceptions and anxiety can cyclically affect performance outcomes (product). For example, students who experience anxiety may revisit questions due to self-doubt, changing correct answers to incorrect ones, which further exacerbates their anxiety and harms overall performance. This cyclical interaction highlights the need to break the negative feedback loop to improve test results. By examining the multifaceted impact of pre-test beliefs, such as overconfidence and perceived difficulty, this research offers insights into how these misperceptions affect test performance by fostering anxiety and maladaptive test-taking strategies. The newly proposed PPP model highlights the operational variability of test-taking strategies across different phases, emphasizing the need for teachers to correct students’ misperceptions to enhance performance. This study provides actionable insights for educators to address psychological needs, mitigate anxiety, and promote better academic outcomes. Future research should test the conceptual framework through empirical investigations to further validate its applicability in educational settings.